Analisis penilaian daur hidup produk screen printing - Ade Astuti Widi Rahayu; Annisa Indah Pratiwi (Universitas Mercu Buana, 2020)
Increasing consumer concern for environmental sustainability is getting bigger, with the issue of green marketing starting to shift from just as added value to being a priority. The emergence of the green consumer and the growing efforts to protect the environment, encourage the industry to consider the environmental impact caused by each of its activities. Industri screen printing is one of the manufacturing companies located in the Surya Cipta industrial area that produces Screen Printing products. In the process of making Screen Printing with one of the items produced, namely named sheet panel can not be separated from the main raw material and support that has chemical elements that have the potential to harm the environment. For this reason, it is necessary to do an evaluation and analysis to determine the value of the environmental impact produced by using the life cycle assessment and life cycle cost method with the support of simapro software so that the value of eco efficiency index (EEI) can be identified from sheet panel products. From this research, it is known that the value of each life cycle assessment and life cycle score is 58.1768704pt at a cost of USD USD 9389,1355 and the value of the eco efficiency index (EEI) sheet panel product is 0.3245, which means that the eco efficiency sheet is affordable but not environmentally friendly (not sustainable).